SRGM with Imperfect Debugging using Capability Analysis of Log-Logistic Model - Naga Raju, Dr.O.; Rakesh, D.; SubbaReddy, K.V. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Analyze the predict capability of some SRGMs to understand the different parameters to facilitate the estimate process. The predict validity analysis will be on two key factors, one pertaining to the degree of fitment on available failure data and the other for its prediction capability. The validity analysis will be to arrive at trade off in choosing a simple model as compared to complex model by determining their performances across multiple data sets. Data for the predict validity analysis has been taken from different time periods to understand the impact of these models across various technologies and process during the time frame.